PERAN EKONOMI KREATIF SEBAGAI SOLUSI MENGATASI PENGANGGURAN - Moh. Idil Ghufron; Moch. Rahmadtullah (Universitas Muhammadiyah Metro Lampung, 2019)
This research discusses the role of creative economy as a solution to overcome and assist economic growth in Indonesia. In this article, focusing on improving human resources to have ideas, creativity, creativity in creating something new or developing that has become something of economic value and can be produced. Besides that, human resources must also use technology to support the results of their creative ideas so that the production process becomes easier and more efficient.In this article, we explain the objectives of economic development and economic growth in Indonesia. In addition, this concept also has a goal to prosper and prosper the people.The method used in this study is literature study, which is a study of the main ingredients of the two components which are the subject of discussion, namely the study of creative economics and economic development. Also added with other books relating to the discussion presented. While the method used is descriptive analytic, namely by gathering actual and detailed information from the data obtained, explained further explained correctly collected, then analyzed directly for the purposes needed for the research made by analyzing content analysis data. Keywords: Creative Economy, Economic Development, Economic Growth, Unemployment.